PolyADP-Ribosylation of NFATc3 and NF-κB Transcription Factors Modulate Macrophage Inflammatory Gene Expression in LPS-Induced Acute Lung Injury - Yunjuan Nie; Teja Srinivas Nirujogi; Ravi Ranjan; Brenda F. Reader; Sangwoon Chung; Megan N. Ballinger; Joshua A. Englert; John W. Christman; Manjula Karpurapu (Karger Publishers, 2020)
Pulmonary macrophages play a critical role in the recognition of pathogens, initiation of host defense via inflammation, clearance of pathogens from the airways, and resolution of inflammation. Recently, we have shown a pivotal role for the nuclear factor of activated T-cell cytoplasmic member 3 (NFATc3) transcription factor in modulating pulmonary macrophage function in LPS-induced acute lung injury (ALI) pathogenesis. Although the NFATc proteins are activated primarily by calcineurin-dependent dephosphorylation, here we show that LPS induces posttranslational modification of NFATc3 by polyADP-ribose polymerase 1 (PARP-1)-mediated polyADP-ribosylation. ADP-ribosylated NFATc3 showed increased binding to iNOS and TNFα promoter DNA, thereby increasing downstream gene expression. Inhibitors of PARP-1 decreased LPS-induced NFATc3 ribosylation, target gene promoter binding, and gene expression. LPS increased NFAT luciferase reporter activity in lung macrophages and lung tissue that was inhibited by pretreatment with PARP-1 inhibitors. More importantly, pretreatment of mice with the PARP-1 inhibitor olaparib markedly decreased LPS-induced cytokines, protein extravasation in bronchoalveolar fluid, lung wet-to-dry ratios, and myeloperoxidase activity. Furthermore, PARP-1 inhibitors decreased NF-кB luciferase reporter activity and LPS-induced ALI in NF-кB reporter mice. Thus, our study demonstrates that inhibiting NFATc3 and NF-кB polyADP-ribosylation with PARP-1 inhibitors prevented LPS-induced ALI pathogenesis.